Obtención de un biopolímero a partir del ácido láctico utilizando como materia prima el almidón de camote - Becerra Miñano, Hugo Gerardo (2006)
The present work of investigation has for fundamental aim(lens) of obtaining a biopolímero from the fermentation of the substratum: flour of yam, which physicist was treated chemically to obtain glucose in a quantity of 14 g/L, which(who) later was fermented to obtain lactic acid, which final concentration of lactic acid in the birreactor was of 0,216 g/L, (being later the final concentration of the lactic acid of 2,162 g/L). The concentrated acid was mixed by a plastificante, agar-agar there being obtained a biodegradable plastic of rugose aspect, which weight of the obtained biopolímero was of 0,2g. Later it was submitted to the test of biodegradabilidad, where the turbidez and presence of bubbles in the biorreactor (CO2, O2), compared with the initial observations indicate the presence of source(fountain) of microorganism, as mud I activate, that is to say qualitative growth of biomass. Finally, this work of investigation specialist will use as guide and tool of consultation for every person and related to the investigation and production(elaboration) of biopolímeros biodegradable. The examples of the designs and presented models serve so much for the use to level of plant(floor) I pilot like to industrial level